THE MACHADO DE ASSIS’ NEW READER - Nasser, Sílvia Maria Gomes da Conceição (Laboratório Editorial FCL-UNESP, 2010)
This work intends to present the reader‟s profile of Machado de Assis‟ two short stories, “Miss Dollar” and “A chave”, that present a concrete image of their readers. The theoretical plateau adopted to create the Machado de Assis‟ short stories reader was based from the Paris School of semiotics. For the analysis of the reading matter, it was chosen the exam of the manifestations of the discourse enunciation, the projection of the enunciator and the enunciate. Also it had the concern to approach the recurrent resources employees, subjects and figures as indicating elements of the profile of the Machado‟s reader.